ChemInform Abstract: Vic‐Tricarbonyl Compounds: Synthesis of (.+‐.)‐9‐epi‐Wailupemycin A. Issue 29 (22nd July 2014) - Seitz, Tobias; Harms, Klaus; Koert, Ulrich
Abstract A synthesis of the title compound (I) is presented, in which a vicinal tricarbonyl compound functioned as key intermediate.